ANALISIS PENGEMBANGAN KOLEKSI PERPUSTAKAAN PASCASARJANA UNIVERSITAS TADULAKO PROVINSI SULAWESI TENGAH - Larabeng, Larabeng (Katalogis, 2018)
This research study about Development collect the Library of PascasarjanaÂ Tadulako of University Palu. Research aim to to identify and analyse the availibility of collection and also factor influencing the availibility of collection in Library of PascasarjanaÂ Tadulako of University Palu. Research have the character of descriptive by using approach qualitative. Analyse the data conducted] by using method interview in measuring and analysing data. Result of research indicate that the collection of library of Pascasarjana Tadulako of University Palu not yet fulfilled the requirement collect the especial teaching substance every which way Pascasarjana Tadulako of University Palu. This Matter because of by some factor, among other things that is not yet maximal co-ordinate between majors party unrightiously is library, and policy of library development arranged by party rektorat. Researcher suggest that the existence of coordination of between library, majors, and dosen in levying collect the library and also the existence of cooperation between party rektorat with the library in the case of conducting development the policy collect.